Sistem Informasi Persediaan Barang Pada PT. Unitera Alfa Elektrindo Medan - Eva Yusnita Barus Hasibuan (Journal of Information System Research (JOSH), 2019)
The system to be designed is a change from what is running in the hope that it can be used to overcome problems, so it is hoped that this information system can be utilized more optimally and is suitable for use. In its operation, this system uses a computer as a tool and is supported by an application program that is made from visual basic and uses Mysql for a database, to input the data needed, such as goods data, supplier data, incoming data and outgoing data data. Thus the results of the system will facilitate the work process of PT. Unitera Alfa Elektrindo Medan, because inventory information needed will be processed faster